Mediatised Culturalisation Through Television: Second-Generation Alevi Kurds in London - Emre Cetin, Kumru Berfin (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
Satellite television has not only provided migrant communities with stronger ties to their home countries but also enabled second-generation migrants in particular to know more about their country of origin beyond their family ties. The aim of this chapter is to explore the ways in which Turkish television contributes towards the making of the transnational identity of the “twice minority” group of Alevi Kurds through what I call mediatised culturalisation. Drawing on 17 in-depth interviews that I conducted with the second-generation members of the Alevi Kurdish community in London in 2016, I explore the role of Turkish television in contesting the boundaries of transnational social imaginaries of the second-generation viewers.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Royaume-Uni (lieu de production du savoir); Turquie (corpus analysé); _Nettoyé

Women’s Fragile Trust: Safety, Familiarity, and Secrecy in the Marriage Show - Akınerdem, Feyza (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
The marriage show was a popular reality show format that invited people to find their soulmate and marry on live television in Turkey. Based on ethnographic fieldwork which took place in the show’s studio between 2011 and 2012, this chapter explores female participants’ investment of their trust in the show. While being reluctant about finding a spouse on television, women take on registers of safety, familiarity, and secrecy to navigate the show as a safe venue. This endeavor also involved women’s safeguarding of themselves on their way to marriage. The fragility of trust in the show, therefore, indicates how women foresee risks and yet strive for securing happiness and safety in marriage in general. This affective tension, at a larger scale, is related to the increased sense of insecurity at a global scale, and the systematic failure of the family to provide the safe living environment it promises in the Turkish context.
Keywords: 1-TV; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Revisiting the Unplugged Margins: Rural Television Audiences and Mediatization - Türkoğlu, Nurçay (Television in Turkey: Local Production, Transnational Expansion and Political Aspirations, 2020)
This chapter examines the social transformation of the television audience of rural Turkey. Villages near a metropolitan area, which were subject to an administrative decision to be relocated, were the focus of my fieldwork 30 years ago. Several visits between 1987 and 2019 to the same location, which is inhabited by television viewers and non-viewers alike, yielded an insightful mapping of engagement with popular culture via television at the periphery in Turkey from a historical perspective. While rural inhabitants are busy with daily labor in the countryside and are not keen on watching television, they are nonetheless aware of and connected to new, nationwide cultural trends and social changes. By reflexively discussing these experiences in ethnographic fieldwork on television habits and reception in rural Turkey over a 30-year span, I avoid the traps of modern-traditional and urban-rural binaries, allowing for an exploration of the role of television in mediating social change in the rural context and thus an analysis of the various complex layers and processes of mediatization among rural audiences.
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

Le soft power à l’épreuve de la réception. Le cas des fictions sérielles turques en Grèce - Larochelle, Dimitra Laurence (Réseaux, 2021)
La production de fictions sérielles turques est en constant développement. Ces fictions ont un très grand succès au niveau local (Tanriöver, 2011 ; Öztürkmen, 2018), avant d’être exportées au-delà des frontières turques depuis les années 2000, d’abord dans des pays sous l’influence culturelle de l’ancien Empire ottoman (à savoir les Balkans et le Moyen-Orient, puis au-delà (en Amérique latine, en Chine, au Pakistan, en Inde, au Bangladesh, etc.), faisant de la Turquie un leader mondial en matière de production et d’exportation. La Grèce est devenue un grand consommateur de fictions sérielles turques et les forts taux d’audience que ces dernières y réalisent ont conduit certains chercheurs à débattre du soft power turc. Plus précisément, en se basant sur les activités des fans des feuilletons en question (comme le tourisme en direction de la Turquie), certains ont soutenu que le visionnage des feuilletons turcs entraîne une amélioration des relations gréco-turques (Paris, 2013). En parallèle, de nombreux articles journalistiques, aussi bien en Grèce que dans d’autres pays, analysent le succès de ces feuilletons auprès du public grec comme une réussite diplomatique du gouvernement turc (Moore, 2013 ; Dimitrakopoulos, 2020).
Keywords: 1-TV; 2-Approches sociologiques; 2-Étude de la réception; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; France (lieu de production du savoir); Grèce (corpus analysé); Turquie (corpus analysé); _Nettoyé

Screening Right-Wing Populism in “New Turkey”: Neo-Ottomanism, Historical Dramas, and the Case of Payitaht Abdulhamid - Bulut, Ergin; İleri, Nurçin (The Routledge Companion to Global Television, 2019)
This chapter examines the intersection of popular culture and populism in Turkey by focusing on the TV show Payitaht Abdulhamid. Our motivation to analyze the recent TV series Payitaht Abdulhamid stems from our interest in the instrumental mobilization of popular culture for the Turkish government’s dual desire to both establish cultural hegemony and consolidate its populist style of government. Our analysis reveals that television, especially in the Global South, still plays a central role in governments’ desire to reconstruct history and establish cultural hegemony. This is particularly important as Turkey is going through a crisis of hegemony since the public is completely divided in its support for the government. Within the context of this hegemonic crisis, televised popular culture is vital, perhaps more than ever. Specifically, the show reduces a complicated history into easily understandable dichotomies and projects them on to contemporary politics in order to consolidate support for the government. Through televised popular culture, the government mobilizes history for purposes of cultural hegemony and populist politics flavored with nationalist, Islamist, and anti-Western motifs. Ultimately, the TV show presents yet another moment for understanding the mediated nature of 21st-century politics outside Western contexts.
Keywords: 1-TV; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice; 5-Créateur.rice PANDC; Turquie (corpus analysé); Turquie (lieu de production du savoir); _Nettoyé

The Carnival of Images : Brazilian Television Fiction - Mattelart, Michèle.; Mattelart, Armand. (Bergin & Garvey, 1990)
In creating and developing the new genre of the televised novela, a one-hour long dramatic serial, the Brazilian television industry grew, in less than 15 years, from an insignificant player in the international market to one of the largest, most influential in the world. In the first book in English to explore the phenomenon of the telenovela Michele and Armand Mattelart challenge accepted views of the world dominance of United States television and probe the socioeconomic impact of this new genre on a third world country. Using the telenovela and its impact on the medium world-wide, the authors document the important changes in the international circulation of television programs and in the way television is perceived theoretically as a subject of research. The book traces the development of the novela in a country that, in the early 1960s, did not have any nationwide media and later--from 1964 to the 1970s--was ruled by a military dictatorship. It further analyzes the formation of the genre and its mode of production, placing the novela's appearance and development in its cultural, institutional, and economic context. The authors look at the peculiar contradictory relation between the genre's creators and developers--generally left wing intellectuals--and the manipulations required to construct a television industry in a highly competitive marketplace. The book begins with a description of the economic, institutional, and cultural context which produced the genre. It explores the world of soap operas, the development of a national television industry, and the beginnings of an urban consumer society in Brazil. The authors include a valuable and detailed study of the mode of production of the telenovela, placing both the form and content of the genre in their specific economic and institutional context. The book goes on to examine the relationship between the genre and its wider social and cultural environment, explaining its immense popularity and the social function it fulfills. Finally, the authors link the study of Brazilian television to wider debates in media and cultural studies.
Keywords: 1-TV; 2-Approches sociologiques; 3-Amérique du Sud (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; Brésil (corpus analysé); France (lieu de production du savoir); _Nettoyé

Sovereign Words: Indigenous Art, Curation and Criticism - García-Antón, Katya (Office for Contemporary Art Norway, 2018)
Artists and cultural practitioners from Indigenous communities around the world are increasingly in the international spotlight. As museums and curators race to consider the planetary reach of their art collections and exhibitions, this publication draws upon the challenges faced today by cultural workers, Indigenous and non-Indigenous, to engage meaningfully and ethically with the histories, presents and futures of Indigenous cultural practices and world-views. Sixteen Indigenous voices convene to consider some of the most burning questions surrounding this field. How will novel methodologies of word/voice-crafting be constituted to empower the Indigenous discourses of the future? Is it sufficient to expand the Modernist art-historical canon through the politics of inclusion? Is this expansion a new form of colonisation, or does it foster the cosmopolitan thought that Indigenous communities have always inhabited? To whom does the much talked-of 'Indigenous Turn' belong? Does it represent a hegemonic project of introspection and revision in the face of today's ecocidal, genocidal and existential crises?"--Page 4 de la couverture. Autres auteurs/titres:edited by Katya García-Antón ; contributors, Daniel Browning, Kabita Chakma, Megan Cope, Santosh Kumar Das, Hannah Donnelly, Léuli Māzyār Luna'i Eshrāghi, David Garneau, Biung Ismahasan, Kimberley Moulton, Máret Ánne Sara, Venkat Raman Singh Shyam, Irene Snarby, Ánde Somby, Megan Tamati-Quennell, Prashanta Tripura, Sontosh Bikash Tripura.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Afrique (lieu de production du savoir); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 4-Asie (lieu de production du savoir); 4-Europe (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé